Ethnic interaction experience of Chinese ethnic students: a case study in Universiti Malaysia Sabah - Budi Anto Mohd Tamring; Natalie Ann Gregory; Romzi Ationg (2020)
In general, countries from all over the world today are showing the intergration between various ethnicities and religions, resulted from migration activities that is done in order to improve life qualities. The integrations has certainly bring in positive and negative impacts due to the differences and similarities in the communities. Major migration by the Chinese and Indian to Malaya, that occured from the policies during British colonial which eventually changed the composition of the population in Malaya and Malaysia, in general. Incidentally, the situation in Sabah which is said to have high ethnic tolerance is likely to affect the attitude and tolerance of the Chinese ethnic in Sabah compared to those in Peninsular Malaysia. Therefore, this study aims to explain the level of student interaction by looking at the tendencies of students in choosing close friends, in their inteactions in academic activites and non-academic activities at the university. Using questionnaires, a total of 215 Chinese students were selected as respondents for this study. The results show that the level of interaction among students is at a moderate level in academic and nonacademic activities, but there are differences between respondents from Sabah compared to the other states. Relatively, Sabahan Chinese students have a higher level of interaction than Peninsular and Sarawakian Chinese students.